'Good Mechanism To Stabilise Prices' - New Sunday Times, (2008)
The government recently announced plans to stockpile essential goods to keep prices down and supply stable Will this work and what will it cost Malaysians ELIZABETH JOHN and ANIZA DAMIS speak to Universiti Putra Malaysia s Dr Mad Nasir Shamsudin and learn from this professor of agriculture and resource economics that it s an idea worth trying.